CONTRIBUTION OF TEACHERS' UNDERSTANDING OF MATHEMATICAL CONCEPTS TO STUDENTS' UNDERSTANDING OF MATHEMATICAL CONCEPTS IN GRADE 3 ELEMENTARY SCHOOL IN BULELENG SUBDISTRICT - ., Ni Made Aristya Dewi; ., Dr.Gede Suweken,M.Sc; ., I Gusti Nyoman Yudi Hartawan, S.Si (Jurnal Pendidikan Matematika Undiksha, 2015)
Penelitian ini bertujuan untuk mengetahui kontribusi pemahaman konsep matematika guru terhadap pemahaman konsep matematika siswa kelas III SD di Kecamatan Buleleng. Penelitian ini merupakan penelitian yang bersifat ex-post facto. Populasi dari penelitian ini adalah kelas III SD di Kecamatan Buleleng yang jumlahnya 87 kelas. Sampel ditentukan dengan teknik Cluster Random Sampling. Hal ini dikarenakan kelas III SD yang diteliti terbagi ke dalam 15 gugus. Dalam penelitian ini, ukuran sampel yang digunakan adalah 21 sampel. Pengumpulan data dilakukan dengan mengadakan tes pemahaman konsep matematika guru dan tes pemahaman konsep matematika siswa. Data yang diperoleh kemudian dianalisis menggunakan analisis korelasi sederhana dan regresi linear sederhana. Hasil penelitian menunjukan bahwa pemahaman konsep matematika guru tergolong baik dengan rata-rata skor 66,67. Pemahaman konsep matematika siswa tergolong cukup baik dengan rata-rata skor 47,87. Selanjutnya, kontribusi pemahaman konsep matematika guru terhadap pemahaman konsep matematika siswa adalah sebesar 25,3%. Artinya, sekitar 25,3% variasi dalam pemahaman konsep matematika siswa dijelaskan oleh pemahaman konsep matematika guru, sedangkan sisanya 74,7% ditentukan oleh variabel lain yang tidak diteliti. Kata Kunci : pemahaman konsep matematika guru, pemahaman konsep matematika siswa The main objective of this research was to determine the contribution of teachers’ understanding of mathematical concepts to students' understanding of mathematical concepts in grade 3 elementary school in Buleleng Subdistrict. This research is an ex-post facto research. Population of this research is all 3rd grade in Buleleng Subdistric consisting of 87 classes. Samples were determined by cluster random sampling technique. This is because the grade 3 which were observed divided into 15 clusters. In this research, the sample size used was 21 samples. Data was collected by using a test of conceptual understanding for teachers and for students. Then the data were analyzed using simple correlation analysis and simple linear regression analysis. The results showed that teachers' understanding of mathematical concepts is good with an average score of 66.67 and students' understanding of mathematical concepts is quite good with an average score of 47.87. Furthermore, the contribution of teachers' understanding of mathematical concepts to students' understanding of mathematical concepts is 25.3%. This means that about 25.3% of the variation in students' understanding of mathematical concepts can be explained by the teacher understanding of mathematical concepts, while the remaining 74.7% is determined by other variables that are not investigated.keyword : teachers’ understanding of mathematical concepts, students' understanding of mathematical concepts